Characterisation of a cysteine protease from bloodstream forms of Trypanosoma congolense - Mbawa, Z.R.; Gumm, I.D.; Shaw, M.; Lonsdale-Eccles, D. (Wiley, 1992)
A cysteine protease (trypanopain‐Tc) with cathepsin‐L‐like properties has been purified from Trypanosoma congolense. The enzyme has an apparent molecular mass of 31–32 kDa by SDS/ PAGE and 66 kDa by gel chromatography. It has a pI 7.4 and a high affinity for concanavalin A. Trypanopain‐Tc catalyses the limited proteolysis of a variety of protein substrates such as fibrinogen, serum albumin and trypanosome variant‐surface glycoprotein. It has minimal or no activity against casein or elastin.A variety of peptidyl amidomethylcoumarins and peptidyl diazomethanes were used to test the specificity of trypanopain‐Tc. The better substrates had Arg or Lys in P1 and hydrophobic amino acids in P2 and P3. The best substrate found for trypanopain‐Tc was Z‐Phe‐Arg‐NHMec (Z, benzyl‐oxycarbonyl; NHMec, 7‐amido‐4‐methylcoumarin). The kinetic constants for the hydrolysis of Z‐Phe‐Arg‐NHMec were kcat= 17.4 s−1, Km= 4.4 μM, kcat/Km= 4.0 μM−1· s−1, which are very similar to those of cathepsin L with this substrate. The specific substrates for cathepsin B (Z‐Arg‐Arg‐NHMec) and cathepsin H (Arg‐NHMec) were not hydrolysed by trypanopain‐Tc under the conditions tested. The pH optimum of trypanopain‐Tc against Z‐Phe‐Arg‐NHMec was pH 6.0 but it showed a broad peak of activity extending well into the alkaline region. The enzyme was activated by low‐molecular‐mass thiol compounds and inhibited by cystatin, L‐trans‐epoxysuccinyl‐4‐guanidinobutane (E‐64) and a variety of peptidyl diazomethanes. The most effective diazomethane inhibitors (Z‐Leu‐Leu‐Met‐CHN2, Z‐Leu‐Met‐CHN2 and Z‐Leu‐Lys‐CHN2, were inhibitory at nanomolar concentrations and were trypanocidal in vitro after 24–48 h incubation in ≥ 20 μM [inhibitor]. However, it is not clear whether the trypanocidal activity of these inhibitors is a consequence of the inhibition of trypanopains or of some other essential proteolytic activities within the parasites.